FT-IR spectroscopy supported by PCA–LDA analysis for the study of embryonic stem cell differentiation. Issue 1 (2010) - Ami, Diletta; Natalello, Antonino; Mereghetti, Paolo; Neri, Tui; Zanoni, Mario; Monti, Manuela; Doglia, Silvia Maria; Redi, Carlo Alberto
Abstract : As recently pointed out in the literature, Fourier transform infrared (FT-IR) spectroscopy is emerging as a powerful tool in stem cell research. In this work we characterized in situ by FT-IR microspectroscopy the differentiation of murine embryonic stem cells (ES) to monitor possible changes in the cell macromolecular content during the early stages of differentiation. Undifferentiated and differentiating cells at 4, 7, 9 and 14 days were measured. Data were analyzed by the principal component and subsequent linear discriminant analyses (PCA–LDA) that enabled us to segregate ES cell spectra into well separate clusters and to identify the most significant spectral changes. Important changes in the lipid (3050–2800 cm –1 ), protein (1700–1600 cm –1 ) and in the nucleic acid (1050–850 cm –1 ) absorption regions were observed between days 4 to 7 of differentiation, indicating the appearance – at day 7 – of the new phenotype into cardiomyocyte precursors. Also the presence of DNA/RNA hybrid bands (954 cm –1 and 899 cm –1 ) suggests that the transcriptional switch of the genome started at this stage of differentiation. Particularly noteworthy, we suggest that the 2936 cm –1 shoulder we observed could reflect methyl group vibrations thus allowing the detection of variations in methylation levels of the stem cell during differentiation. These infrared results were found to be in agreement with the biochemical characterization of these differentiating cells, underlying the great potential of FT-IR spectroscopy in stem cell research.